"If only he were blind": Shame, trauma, and dissociation among women with body dysmorphic disorder in physically intimate relationships. Issue 1 (31st December 2022) - Stechler, Natalie; Henton, Isabel
ABSTRACT: Background: Body Dysmorphic Disorder (BDD) involves a debilitating preoccupation with one's appearance and associated difficulties in social and interpersonal relationships, according to the Diagnostic and Statistical Manual for Mental Disorders (DSM-5). Quantitative research has investigated the severity of relationship difficulties in BDD, while qualitative research has primarily focused on intrapersonal phenomena, although interpersonal difficulties, including with physical intimacy, have frequently emerged from these studies. Aims: This study explores how women with BDD make sense of their lived experiences of physical intimacy in the context of current partner relationships. Method: Six adult women participated in individual semi-structured interviews. The data was analysed using Interpretative Phenomenological Analysis. Results: The analysis generated three superordinate themes: 1) The shame in being seen, 2) Disgust and detachment during intimacy, and 3) A flawed self, unworthy of relationships. Conclusions: This study demonstrates how appearance-related concerns filter into the cognitive, behavioural, and emotional intersubjective spaces of physically intimate partnerships. Shame or trauma may be triggered and may be managed through disengagement or dissociation. Clinical implications: These findings support calls for a full psychological assessment of the contextual and interpersonal components of BDD, and further suggest that psychological interventions for shame, trauma, and dissociation, such as compassion-focused therapy, imagery rescripting, or body-focused therapies, may be helpful additions to cognitive-behavioural or exposure and response prevention interventions for practitioners working with BDD.